Experimental investigation on the beam quality improvement of the fiber laser by adaptive optics. (18th November 2015) - Bian, Q; Huang, L; Wang, X J; Ma, X K; Yan, P; Gong, M L
Abstract: This paper describes an adaptive optical system that is introduced to improve the beam quality of a fiber laser. Since a distorted wavefront would degrade the beam quality of a laser beam, a deformable mirror is employed to compensate for the wavefront aberration using closed-loop control in this system. The beam quality factor is measured and the far-field focus spot is detected as well. The experiment results show that the beam quality factor can be improved from 5–7 to 3–4 and the focus spot can be improved as well. The feasibility of the system is proved.